The Effects of a Multi-Ingredient Performance Supplement on Hormonal Profiles and Body Composition in Male College Athletes - Matthew H. Sharp; Kevin A. Shields; Jacob T. Rauch; Ryan P. Lowery; Shane E. Durkee; Gabriel J. Wilson; Eduardo O. De Souza (MDPI AG, 2016)
Periods of intense training can elicit an acute decline in performance and body composition associated with weakened hormone profiles. This study investigated the effects of a multi-ingredient performance supplement (MIPS) on body composition and hormone levels in college athletes following a six-week training protocol. Twenty male college athletes were equally assigned to MIPS and placebo (PLA) groups for supplementation (three pills, twice daily) in conjunction with resistance training and specialized sports training (e.g., nine total sessions/week) for six weeks. Dual Energy X-ray Absorptiometry determined body composition at weeks 0 and 6. Serum samples collected at weeks 0 and 6 determined free testosterone (FT), total testosterone (TT), IGF-1 and total estrogen (TE) levels. PLA experienced a significant decline in lean body mass (LBM) (−1.5 kg; p < 0.05) whereas the MIPS sustained LBM. The MIPS increased TT 21.9% (541.5 ± 48.7 to 639.1 ± 31.7) and increased FT 15.2% (13.28 ± 1.1 to 15.45 ± 1.3 ng/dL) (p < 0.05). Conversely, PLA decreased TT 7.9% (554.5 ± 43.3 to 497.2 ± 39.1 ng/dL), decreased FT 17.4% (13.41 ± 1.8 to 11.23 ± 2.55 ng/dL), and decreased FT:E 12.06% (p < 0.05). These findings suggest the MIPS can prevent decrements in LBM and anabolic hormone profiles during intense training periods.